Clustering and switching in divergent thinking: Neurophysiological correlates underlying flexibility during idea generation. (30th July 2021) - Mastria, Serena; Agnoli, Sergio; Zanon, Marco; Acar, Selcuk; Runco, Mark A.; Corazza, Giovanni Emanuele
Abstract: EEG alpha synchronization, especially in posterior parietal cortical regions of the right hemisphere, is indicative of high internal processing demands that are typically involved in divergent thinking (DT). During the course of DT, as ideation proceeds, ideas tend to become more creative, being more likely to be drawn from new conceptual categories through the use of the cognitive mechanism of flexibility. The present study investigated whether EEG alpha synchronization can be modulated by flexibility in DT by comparing cortical activation patterns during the switch of category (switching) and the stay in the same category (clustering). Twenty participants were required to generate alternative uses of everyday objects during EEG recording. Differential results were specifically found in the lower alpha band (8–10 Hz): whereas clustering showed synchronization typically lateralized in the right posterior parietal areas, switching induced posterior parietal synchronization over both right and left hemispheres. These findings indicate that the two distinct cognitive mechanisms subsuming flexibility (switching and clustering) are associated with a different hemispheric modulation of lower alpha activity, as switching, in comparison to clustering, is related to higher power in the lower alpha band over the left hemisphere. Switching in comparison to clustering may thus require a larger investment of cognitive resources due to the exploratory process of moving from one semantic conceptual category to another in the course of creative ideation. Highlights: Alpha band underlying switching and clustering in creative thinking was explored. Participants performed a structured version of an Alternative Uses Test (AUT). Differential results were found in the lower alpha than in the upper alpha band. Switching, than clustering, induced bilateral parietal lower alpha synchronization. Switching and clustering reflect different brain mechanisms in creative ideation.